Foundation engineering - Peck, Ralph B. (Ralph Brazelton); Thornburn, Thomas H.; Hanson, Walter E. (New York : John Wiley and Sons, 1974)
The scope of the book has been enlarged to include discussions of foundations on rock, on swelling soils, on fill and on flexible earth-retaining structures such as braced and tieback walls and anchored bulkheads.
Keywords: Foundations; Engineering; Foundations